2020 International Symposium on Electronics and Telecommunications (ISETC) 2020
DOI: 10.1109/isetc50328.2020.9301124
|View full text |Cite
|
Sign up to set email alerts
|

IoT Based Intelligent Building Applications in the Context of COVID-19 Pandemic

Abstract: COVID-19 (Coronavirus) has affected our day to day life and the global economy and is far from being over. COVID-19 continues to spread rapidly around the world, more with the relaxation of restriction measures imposed by most countries. Limiting the further community spread of the epidemic has become a crucial issue, as employees return to office buildings. Technology, and especially intelligent building technology, can help to this purpose. Smart devices will have an important role to play in determining how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Moreover, Fazio et al developed an internal navigation system based on BIM that assists users in navigating smart buildings by tracking their location over time and recommending the most efficient route to their destination [ 154 ]. What is more, Bogdan-Petru et al presented a system equipped with IoT that would enable office users to handle office items remotely without touching them, such as opening and closing the entry door, controlling lighting, and operating the coffee machine [ 155 ]. Additionally, Swinarski et al simulated occupants’ behaviours in an educational building to evaluate the four different interventions for elevator operation [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Fazio et al developed an internal navigation system based on BIM that assists users in navigating smart buildings by tracking their location over time and recommending the most efficient route to their destination [ 154 ]. What is more, Bogdan-Petru et al presented a system equipped with IoT that would enable office users to handle office items remotely without touching them, such as opening and closing the entry door, controlling lighting, and operating the coffee machine [ 155 ]. Additionally, Swinarski et al simulated occupants’ behaviours in an educational building to evaluate the four different interventions for elevator operation [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in this review demonstrated that intelligent sensors, cameras, and artificial intelligence (AI) technologies could be integrated with building management systems (BMI) to facilitate infection control activities, such as occupant movement tracking [ 154 ], occupant counting, social distance and face masking monitoring, and the detection of feverish occupants [ 132 ]. Moreover, multiple articles have demonstrated how BIM and IoT-based apps could be used to visualise space occupancy [ 153 ], enabling occupants to reserve seats and control office facilities remotely [ 155 ] and facilitate social distancing [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the IoT enables monitoring patients' chronic diseases that increase the risk of death caused by the COVID-19 virus. Therefore, there are many possibilities of using IoT technologies such as those that enable one to avoiding touching various objects and surfaces in offices [11]. R.P.…”
Section: Figure 2 the Most Frequently Used Emerging Technologies For Mitigating The Impact Of The Covid-19 Pandemicmentioning
confidence: 99%
“…IoT usually uses several devices such as microcontrollers or microprocessors. The microcontroller commonly used in the IoT systems is ESP-32 [22] or ESP8266 [23], and the microprocessor often used in IoT development is the Raspberry Pi [24].…”
Section: B Internet Of Things (Iot)mentioning
confidence: 99%